How to properly define immunological nonresponse to antiretroviral therapy in people living with HIV? an integrative review - Guedes, Maria Carolina Santos; Lopes-Araujo, Henrique Fernando; dos Santos, Kleyverson Feliciano; Simões, Esaú; Carvalho-Silva, Wlisses Henrique Veloso; Guimarães, Rafael Lima (Frontiers in Immunology, 2025)
In recent decades, significant progress has been made in understanding the mechanisms underlying human immunodeficiency virus (HIV) infection and its treatment. Antiretroviral therapy (ART) has notable improved the life expectancy and quality of life for people living with HIV (PLHIV) by suppressing viral replication and promoting CD4+ T-cell recovery. However, despite its efficacy, approximately 10-40% of ART-treated PLHIV with virological suppression (<50 RNA copies/mL) do not achieve adequate immunological reconstitution. These PLHIV, classified as immunological non-responders (INR), experience higher morbidity and mortality rates compared to those with satisfactory immune reconstitution, known as immunological responders (IR). Various studies have explored the mechanisms contributing to immunological nonresponse, yet a major challenge remains: the lack of a standardized definition of immunological response and nonresponse across studies. Currently, definitions are inconsistent, limiting comparability between studies. This review proposes a clear and adequate classification for IR and INR PLHIV to support future advancements in understanding immunological recovery and improving the quality of life for ART-treated PLHIV.